Impact of Sea Product Zakat Distribution on The Economy of Coastal Communities (Case Study Fisherman Yogyakarta) - Hasbi, M. Zidny Nafi'; Widayanti, Ipuk (Universitas Islam Negeri Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2022)
Indonesia as one of the largest maritime countries in the world has enormous potential. To overcome this, it is necessary to optimize zakat. In this context, it is necessary to develop seafood zakat products through a productive distribution model so that the potential for community empowerment is realized. The purpose of this study is to identify and develop a distribution model of marine product zakat based on public perception. This research method is qualitative with a comparative study approach. Data collection techniques include observation, documentation, and deep interviews. The object of this research is the coastal communities located on the coast of Depok and the coast of Gunung Kidul, Yogyakarta. The results showed that the zakat on marine products from fishermen was not realized due to the lack of knowledge about the zakat distribution model and there was no collection of zakat funds for marine products. The solution offered by the researcher is to create a model for the distribution of zakat on marine products that will be collected by an organization called the